Metabolically healthy overweight/obesity are associated with increased risk of cardiovascular disease in adults, even in the absence of metabolic risk factors: A systematic review and meta-analysis of prospective cohort studies - Opio, Jacob; Croker, Emma; Odongo, George S.; Attia, John; Wynne, Katie; McEvoy, Mark (Obesity Reviews, 2020)
This review examined the risk of cardiovascular disease in adults with metabolically healthy overweight/obesity. A systematic review and meta-analysis using data from Medline, EMBASE, SCOPUS and Cochrane Library searched from inception up to 31st October 2019. We included prospective cohort studies of adults who are metabolically healthy or unhealthy. Outcomes were fatal and nonfatal cardiovascular events, all-cause mortality. Pooled relative risk was calculated for each outcome in populations with metabolically healthy overweight and metabolically healthy obesity using metabolically healthy normal weight as reference. A random-effects model was used for meta-analysis, and risk of bias assessment tool for nonrandomized studies assessed risk of bias within each study. Twenty-three prospective cohort studies with 4,492,723 participants were included. Cardiovascular disease risk was increased in metabolically healthy groups with overweight (RR = 1.34, CI: 1.23–1.46, n = 20, I2 = 90.3%) and obesity (RR = 1.58, CI: 1.34–1.85, n = 21, I2 = 92.2) compared with a reference group with metabolically healthy normal weight. Cardiovascular disease risk was similar irrespective of the number of risk factors used to define metabolically healthy and the risk remained in the group with no metabolic risk factors. Cardiovascular disease risk is increased in populations with overweight and obesity classified as metabolically healthy even when there were no metabolic risk factors.
Keywords: Prospective cohort studies; Metabolic risk factors; Cardiovascular disease